PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PT MATAHARI DEPARTEMENT STORE CABANG MALL PANAKUKANG MAKASSAR - Nafila Oktavia; Syamsul Alam; Asri Asri (AkMen JURNAL ILMIAH, 2020)
This research is a quantitative study with a survey method approach in data collection. This study aims to determine the effect of work environment, compensation, motivation on employee performance through job satisfaction at PT Matahari Department Store, Mall Panakukang Makassar branch. The population used in this study were 100 employees of PT Matahari Department Store, Panakukang Mall Makassar branch. While the sample is determined based on the provisions of the saturated sample, which takes all elements of the population to be the research sample. The analytical method used is path analysis. The results showed (1) Work environment, compensation, and motivation have a positive and significant effect on employee job satisfaction at PT Matahari Department Store, Mall Panakkukang Makassar Branch (2) Work environment, compensation, and motivation have a positive and significant effect on employee performance at PT Matahari Department Store Branch Mall Panakkukang Makassar (3) Work environment, compensation, and motivation have a positive and significant effect on employee performance through job sati.